Covid-19 vaccination certificates and lifting public health and social measures: ethical considerations - Voo, Teck Chuan (2022)
As countries roll out their COVID-19 vaccination programs, a policy question to consider is whether, and under what conditions, it would be acceptable to lift or ease non-pharmaceutical public health measures such as social distancing and movement-related restrictions specifically for individuals who have been administered a COVID-19 vaccine. Broadly, such policies would aim to restore a range of liberties, which have been restricted in varying degrees to control disease spread in many societies, to vaccinated individuals. Where a substantial portion of a society has been vaccinated, the restoration of liberties to vaccinated individuals could help restore social and economic activities, and confer benefits and alleviate the burdens of the public health measures on individuals, businesses, and communities. The implication of such policies, however, is that vaccinated individuals would be treated differently from non-vaccinated individuals and enjoy a broader range of civil and other liberties (so-called ?special? rules or privileges) not accorded to the latter.1 One main ethical concern is that such differential restrictions may introduce or exacerbate inequities for non-vaccinated individuals, depending on the policies and rules set up. This paper provides an analysis of the ethical issues in introducing a different set of rules for COVID-19 vaccinated individuals with respect to COVID-19 restrictive measures.